The effects of the COVID‐19 pandemic on weight loss in participants in a behavioral weight‐loss intervention. Issue 5 (12th April 2022) - Zaman, Adnin; Sloggett, Kelsey J.; Caldwell, Ann E.; Catenacci, Victoria A.; Cornier, Marc‐Andre; Grau, Laura; Vetter, Céline; Rynders, Corey A.; Thomas, Elizabeth A.
Abstract: Objective: This study aimed to assess the effects of the COVID‐19 pandemic on weight loss, physical activity, and sleep in adults with overweight or obesity participating in a 39‐week weight‐loss intervention. Methods: Participants ( n = 81, 85% female, mean [SD] age 38.0 [7.8] years, BMI 34.1 [5.7] kg/m 2 ) were enrolled in 3 separate cohorts. Cohorts 1 and 2 were studied prior to the pandemic (pre‐COVID cohorts). Cohort 3 (COVID cohort) transitioned to a virtual intervention at week 6, when "stay‐at‐home" orders were implemented in Colorado. Weight was assessed at baseline, week 12, and week 39 with clinic scales before the pandemic and home scales during the pandemic. Diet was assessed with Likert scales at weeks 4, 8, and 12. Physical activity and sleep were assessed at baseline and week 12 with actigraphy. Results: Participants in the COVID cohort reported greater dietary adherence ( p = 0.004) and lost more weight than those in the pre‐COVID cohorts at week 12 (−7.7 [3.3] kg vs. −3.7 [3.0] kg, p < 0.001) and week 39 (−8.5 [4.4] kg vs. −2.8 [4.6] kg, p < 0.001). Energy intake did not differ between cohorts ( p = 0.51). The COVID cohort increased both sedentary time while awake and time in bed at night. Conclusions: Although the pandemic caused disruptions for the COVID cohort, participants still achieved weight loss with continued behavioral support.